Atividade biofloculante de bactérias isoladas de painéis fotovoltaicos e aplicação no condicionamento do lodo de esgoto - Nascimento, Letícia Portugal do (2023)
The dewatering process of sewage sludge is a fundamental part of wastewater treatment. However, it is negatively affected due to the amount of suspended solid particles and water content retained by extracellular polymeric substances. The usage of additives during sewage sludge conditioning is an approach to promote the destabilization of the colloidal system and the aggregation of particles, enhancing water removal. Bioflocculants synthesized by bacteria may be a promising substitute for commercial flocculants because of their non-toxicity and biodegradability. This current research investigated the production of biosurfactants by Sphingomonas paucimobilis, Serratia nematodiphila, Kocuria sp., and Psychrobacter sp., previously isolated from solar panels, and their flocculant activity when applied to sewage sludge conditioning process. Since extremophiles are evolutionarily adapted to survive under harsh conditions, they may be a valuable source of biotechnological relevant byproducts such as bioflocculants. All bacteria assessed in the current work presented flocculant ability when applied to kaolin suspension, but Psychrobacter sp. was selected for further analysis because of its high stability and efficiency. The bioflocculant was characterized as being mainly composed of sugars (24.64%), lipids (18.10%), and proteins (10.23%). The FTIR spectrum revealed the presence of amine, hydroxyl, and carboxyl functional groups, which are responsible for the flocculant properties of the molecule. The bioflocculant was applied in the conditioning process of aerobic sludge samples, collected from an aeration tank, and anaerobic sludge samples, collected from an Upflow Anaerobic Sludge Blanket, reaching 92.96% and 71.53% of flocculation efficiency, respectively. Furthermore, the bioflocculant was as effective as a commercial cationic polymer commonly used during wastewater treatment. Hence, this molecule may be a promising substitute for commercial additives in wastewater treatment. However, further economic analyses are needed, especially regarding alternative carbon sources.